PKM REVITALISASI BANK SAMPAH DALAM MENUMBUHKAN SOCIALPRENEURSHIP BERBASIS MODUL HYPERCONTENT - Budiaman; Cecep Kustandi; Aam Amaningsih Jumhur (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
Abstract The Ministry of Environment and Forestry (LHK) noted that East Jakarta has the highest annual waste generation in DKI Jakarta, reaching 836.9 thousand tons per year, with the largest contribution to the Bantargebang TPST of 620.96 thousand tons (27.14% of total waste) in 2021. The pandemic has changed people's consumption patterns with the increasing use of double wrapping, which adds to the problem of non-organic waste. The student council management owned by the partner school, SMP Negeri 158 East Jakarta, consists of students who have more awareness of environmental management. This activity was developed in an effort to protect the environment and generate economic value for each member. This concept of socialpreneurship takes advantage of business opportunities in the community to have a positive impact, focusing on the problem of high-economic value waste production and the marketing of plastic ore from plastic bottles that have been grouped. The solutions offered to these problems are in the form of assistance for school leaders and Adiwiyata coaches in fostering student socialpreneurship, empowering student council administrators to sort non-organic waste with high economic value using hypercontent modules, and revitalizing school waste banks with an inventory of equipment such as shredders, drop boxes, and greenhouses. This activity was carried out by involving partners through observation and FGD at SMP Negeri 158 East Jakarta and simulations at the Pok Lisa Waste Bank to understand the process of processing plastic waste that has economic value. Keywords: socialpreneurship; revitalizing; waste bank; Hypercontent Abstrak Kementerian Lingkungan Hidup dan Kehutanan (LHK) mencatat bahwa Jakarta Timur memiliki timbulan sampah tahunan tertinggi di DKI Jakarta, mencapai 836,9 ribu ton per tahun, dengan kontribusi terbesar ke TPST Bantargebang sebesar 620,96 ribu ton (27,14% dari total sampah) pada 2021. Pandemi mengubah pola konsumsi masyarakat dengan meningkatnya penggunaan double wrapping, yang menambah masalah sampah non-organik. Pengurus OSIS yang dimiliki oleh sekolah mitra yaitu SMP Negeri 158 Jakarta Timur beranggotakan siswa-siswi yang memiliki kesadaran lebih terhadap pengelolaan lingkungan. Kegiatan ini dikembangkan dalam upaya menjaga lingkungan serta menghasilkan nilai ekonomi untuk setiap anggotanya. Konsep socialpreneurship ini memanfaatkan peluang bisnis di tengah masyarakat untuk memberi dampak positif, dengan fokus pada masalah produksi sampah bernilai ekonomi tinggi dan pemasaran bijih plastik dari botol plastik yang sudah dikelompokkan. Solusi yang ditawarkan untuk permasalahan tersebut berupa pendampingan bagi pimpinan sekolah dan pembina Adiwiyata dalam menumbuhkan socialpreneurship siswa, pemberdayaan pengurus OSIS untuk memilah sampah non-organik bernilai ekonomi tinggi menggunakan modul hypercontent, serta revitalisasi bank sampah sekolah dengan inventarisasi peralatan seperti mesin pencacah, drop box, dan rumah kaca. Kegiatan ini dilaksanakan dengan melibatkan mitra melalui observasi dan FGD di SMP Negeri 158 Jakarta Timur serta simulasi di Bank Sampah Pok Lisa untuk memahami proses pengolahan sampah plastik yang memiliki nilai ekonomi. Kata Kunci: socialpreneurship; revitalisasi; bank sampah; Hypercontent